Gestão transversal das políticas públicas no âmbito federal: uma leitura inicial - Reinach, Sofia (2013)
Although the term transversality has been widely used in Brazil, many doubts are still raised about its meaning. The literature swings from explaining transversality as an idea merely imported from the most used idea of gender mainstreaming used in Europe and the debate about different types of public management. However, little is discussed about how to put this idea into practice and which implications derive from that. The term transversality is frequently used in debates about policies against men and women inequality, mostly related to gender mainstreaming. In the Brazilian government, between 2003 and 2012 (period covered by this research), there were three departments recognized as being agents of transversal policies: the Secretariat for Women Policies (SPM), the Secretariat for Human Rights (SDH) and the Secretariat of Policies for Equal Racial Promotion (SEPPIR). It describes the historic development of the Brazilian state departments as well as the three Secretariats. The gender mainstreaming proposals are also included both as an international influence and as an important Brazilian policy. These three Secretariats were created in 2003, in order to act integrated with other governmental departments and to have different competencies and resources as the Ministries. Some of the Secretariat managers were interviewed in order to describe their views of transversality in their daily routine. The meaning and uses of transversality in practical work and its implication were analyzed. The managers’s speeches about transversality were used to discuss the fight against a “wicked problem” in public management. A multidimensional management is suggested to deal with this question.